Theologies of Childhood and the Children of Africa - Grobbelaar, Jan; Breed, Gert (AOSIS, 2017)
The purpose of this book is to combine perspectives of scholars from Africa on Child Theologies from a variety of theological sub-disciplines to provide some theological and ministerial perspectives on this topic. The book disseminates original research and new developments in this study field, especially as relevant to the African context. In the process it addresses also the global need to hear voices from Africa in this academic field. It wants to convey the importance of considering Africa's children in theologising. The different chapters represent diverse methodologies but the central and common focus is to approach the subject from the viewpoint of Africa's children. The individual authors' varied theological sub-disciplinary dispositions contribute to the unique and distinct character of the book. Almost all chapters are theoretical orientated with less empirical research, although some of the chapters refer to empirical research which the authors have done in the past.